2001
DOI: 10.1104/pp.126.2.643
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis ATHB-8 HD-Zip Protein Acts as a Differentiation-Promoting Transcription Factor of the Vascular Meristems

Abstract: ATHB-8, -9, -14, -15, and IFL1/REV are members of a small homeodomain-leucine zipper family whose genes are characterized by expression in the vascular tissue. ATHB-8, a gene positively regulated by auxin (Baima et al., 1995), is considered an early marker of the procambial cells and of the cambium during vascular regeneration after wounding. Here, we demonstrate that although the formation of the vascular system is not affected inathb8 mutants, ectopic expression of ATHB-8 in Arabidopsis plants increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
340
2
10

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(361 citation statements)
references
References 38 publications
9
340
2
10
Order By: Relevance
“…Microscopic investigation of this phenomenon using trypan blue-stained leaves sampled at 21 DAI showed that chloroplast-containing bundle sheath cells enveloping the vascular bundles in wild-type leaves ( Figure 1F a dramatic reduction of xylem parenchyma cells and disappearance of the continuous cambial zone in all investigated tissues, suggested that hyperplastic xylem formation was caused by preceding xylem parenchyma cell transdifferentiation and transient reinitiation of cambial activity. The latter conclusion was confirmed by enhanced expression of the cambial marker gene ARABIDOPSIS THALIANA HOMEOBOX GENE8 (At-HB8) (Baima et al, 2001), which in leaves already started at 7 DAI and peaked at 14 DAI ( Figure 3A). As a consequence, radial autofluorescent cell files were produced, which distorted the phloem tissue and displaced the vascular tissue borders (Figures 2D and 2F).…”
Section: Longisporum Infection Induces De Novo Formation Of Functimentioning
confidence: 64%
“…Microscopic investigation of this phenomenon using trypan blue-stained leaves sampled at 21 DAI showed that chloroplast-containing bundle sheath cells enveloping the vascular bundles in wild-type leaves ( Figure 1F a dramatic reduction of xylem parenchyma cells and disappearance of the continuous cambial zone in all investigated tissues, suggested that hyperplastic xylem formation was caused by preceding xylem parenchyma cell transdifferentiation and transient reinitiation of cambial activity. The latter conclusion was confirmed by enhanced expression of the cambial marker gene ARABIDOPSIS THALIANA HOMEOBOX GENE8 (At-HB8) (Baima et al, 2001), which in leaves already started at 7 DAI and peaked at 14 DAI ( Figure 3A). As a consequence, radial autofluorescent cell files were produced, which distorted the phloem tissue and displaced the vascular tissue borders (Figures 2D and 2F).…”
Section: Longisporum Infection Induces De Novo Formation Of Functimentioning
confidence: 64%
“…These 2 families can be distinguished by a fifth domain, the C-terminal MEKHLA motif, which is present in the HD-ZIP III subfamily and absent in the HD-ZIP IV subfamily (Mukherjee and Bürglin, 2006). The HD-ZIP III subfamily comprises only 5 genes in Arabidopsis, ATHB8, PHAVOLUTA (PHV)/ATHB9, PHABULOSA (PHB)/ATHB14, REVOLUTA (REV)/INTERFASCICULARFIBERLESS1 (IFL1), and CORO-NA (CNA)/ATHB15/INCURVATA4 (ICU4) (Prigge et al, 2005), but they are the key developmental regulators of Arabidopsis apical embryo and shoot radial patterning, shoot meristem formation, vascular differentiation, lateral organ polarity development, and auxin transportation (Baima et al, 2001;McConnell et al, 2001;Emery et al, 2003;Ohashi-Ito and Fukuda, 2003;Prigge et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Three members of this family of genes, PHAVOLUTA, PHABULOSA, and REVOLUTA, are involved in determining adaxial identity in leaves and embryos (Talbert et al, 1995;McConnell and Barton, 1998;McConnell et al, 2001;Otsuga et al, 2001;Emery et al, 2003;Prigge et al, 2005). Expression and functional data for the other two members of this class, ATHB8 and ATHB15/CNA, suggest that they play roles in vascular development, with ATHB15/CNA possibly having roles in establishing embryonic and vascular polarity (Baima et al, 1995;Baima et al, 2001;Ohashi-Ito and Fukuda, 2003;Prigge et al, 2005). Based on the functional analyses to date, this class of HDs appears to have a common role in establishing and/or maintaining abaxial/adaxial polarity.…”
mentioning
confidence: 99%